Biochemical Processes of Chlorella vulgaris and Their Impact on Chlorophyll Quality and Antioxidant Properties - Iriani, Dian; Feliatra; Hasan, Bustari; Karnila, Rahman; Chaiyanate, Nittaya; Rozi (Jurnal Ilmiah Perikanan dan Kelautan, 2025)
Graphical Abstract Highlight Research Chlorella indigenous from waters of Rokan River estuary was identified. The using of 4 chemicals KNO3, KH2PO4, MgSO4.7H2O and FeSO4.7H2O can reduce production cost and obtain an optimal medium formulation. The manipulated media was obtained can replace the commercial media of Chlorella Chlorella vulgaris contains high antioxidant activity.   Abstract Chlorella is a microalga that is rich in chlorophyll and antioxidants so it has the potential to be a functional food or health supplement; however, the quality of Chlorella depends on the nutrient composition in cultivation. The research aimed to evaluate the effect of different formulations in Chlorella cultivation on the content of chlorophyll a, chlorophyll b, total chlorophyll, carotenoids and antioxidants. Furthermore, to analyse the profile of amino acids, fatty acids and secondary metabolism in the best formulation. The experimental design used was a non-factorial Completely Randomized Design (CRD) with 5 formulations in Chlorella cultivation: F-1, F-2, F-3, F-4, and F-5 by manipulating the use of 4 chemicals: KNO3, KH2PO4, MgSO4.7H2O and FeSO4.7H2O. The data obtained were analyzed descriptively and analysis of variance (ANOVA). The results showed that F-2 treatment with the use of 1.50 KNO3, 1.25 KH2PO4, 1 MgSO4.7H2O and 0.0498 FeSO4.7H2O (g/L) was the best treatment with the content of chlorophyll a 38.19 μg/mL, chlorophyll b 41.45 μg/mL, total chlorophyll 79.65 μg/mL, carotenoids 0.08 μg/mL, and antioxidants activity 49.52 mg/L (strong) which is the same as the F-1 treatment. In addition, Chlorella cultivated with the F-2 formula has 17 amino acid profiles with a total of 301.52 mg/g, 7 fatty acids 84.32 mg/g, and secondary metabolites, namely alkaloid 109.471 mg/L, flavonoid 82.111 mg/L, saponin 1342.222 mg/L, tannin 411,591 mg/L, and phenolic 151.889 mg/L. Therefore, the F-2 formulation can be developed for large-scale Chlorella cultivation and applied as a health supplement.